2021
DOI: 10.1109/access.2021.3100429
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based TF Colorization With CNN for Direct Volume Rendering

Abstract: In the direct volume rendering (DVR), it often takes a long time for a novice to manipulate the transfer function (TF) and analyze the volume data. To lessen the difficulty in volume rendering, several researchers have developed deep learning techniques. However, the existing techniques are not easy to apply directly to existing DVR pipelines. In this study, we propose an image-based TF colorization with CNN to automatically generate a direct volume rendering image (DVRI) similar to a target image. Our system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, a larger experiment is needed since the experiment was only evaluated using a few datasets. [17]. Shi, Q (et al) describe a VGG-16 Convolutional network model that uses a fully autonomous learning-based colorisation technique based on cross-entropy loss in classification generating plausible colour images while mainly focusing on reducing image quality loss [18].…”
Section: Related Workmentioning
confidence: 99%
“…However, a larger experiment is needed since the experiment was only evaluated using a few datasets. [17]. Shi, Q (et al) describe a VGG-16 Convolutional network model that uses a fully autonomous learning-based colorisation technique based on cross-entropy loss in classification generating plausible colour images while mainly focusing on reducing image quality loss [18].…”
Section: Related Workmentioning
confidence: 99%
“…Liao et al [12] demonstrated that similar data attributes of images can be transferred through dense correspondence. Kim et al [13] proposed training a convolutional neural network to determine the transfer function grid for labeling and extract the primary color from the target image. He et al [14] proposed learning colorings using an end-to-end neural network, eliminating the need for human-made coloring rules.…”
Section: Related Workmentioning
confidence: 99%